For Kantians Only? Arthur Petersen on Transcendental Naturalism, Climate Change, and God - van den Brink, Gijsbert (Zygon, 2025)
In this article, after expressing my appreciation for the novelty, timeliness, and openness of Arthur Petersen’s approach in his Climate, God and Uncertainty, I discuss a main concern raised by the book, namely, its heavy reliance on a Kantian dualism between knowledge and faith. Drawing on Immanuel Kant’s contemporary Thomas Reid, and helped by present-day scholarship on Reid, I propose an alternative epistemology, which, if accepted by Petersen, would enable him to include not only (hopefully) Kantians but also the majority of adherents of the great monotheistic traditions (that is, all of them who think it is possible to know God) in his camp. This is of crucial importance, since Petersen’s plea for a nature-sensitive spirituality that breaks the collective patterns of behavior that have led to the contemporary climate crisis by addressing the deepest layers of human existence is very timely and worthwhile.